Podejście procesowe we wdrażaniu systemów zarządzania bezpieczeństwem informacji - Wawak, Sławomir (A Process Approach to Implementation of Information Security Management Systems, 2009)
Information security management systems are applicable in computer and telecommunications services, public administration and self-government administration. Top management of organization, while beginning implementation of ISMS usually covers only technical problems of information security, which can be solved by computer experts. Only a few of managers are aware of organizational problems connected with specificity of products or services. In this article, a process approach to implementation of ISMS was discussed. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 127-135